Ketersediaan Hayati Isoflavon dalam Plasma dan Pengaruhnya Terhadap Nilai Biokimia Darah pada Tikus Hiperglikemia (BIOAVAILABILITY OF ISOFLAVONE PLASMA AND THEIR EFFECT OF THE VALUE OF BLOOD BIOCHEMISTRY IN HYPERGLYCEMIC RAT ) - Suarsana, I Nyoman; Widyastuti, Srikayati; Priosoeryanto, Bambang Pontjo (Jurnal Veteriner, 2012)
Isoflavone compounds have been known to have biological effects in improving health. The purpose ofthis study was to determine the bioavailability of isoflavone in plasma and its role as lowering bloodglucose levels in hyperglycemia rats. Bioavailability of isoflavones in plasma was performed in 18 ratsstrains Spraque Dawley age 3 months with 200 g of body weight on average and were given 300 ppm oralof isoflavone single dose. The analysis of isoflavon as done at 0, 1, 6, 12, 18 and 24 hours using HPLCmethod. Study effect on blood biochemical values used 25 male rats, which was divided into 5 treatmentgroups. One group as a negative control (K1) was given aquades; positive group hyperglycemia (K2), and 3other groups (K3, K4 and K5) were a positive groups of hyperglycemia and given isoflavone different doses,i.e. 1.0, 1.5 and 2.0 mg/200g bw per oral. Blood glucose were analyzed by using glucose oxidase biosensor,while cholesterol, HDL (Hight-density lipoprotein) and triglycerides were analyzed enzymatically using aspectrophotometer. The results showed the analyzes isoflavone genistein was more efficiently absorbedthan daidzein and glisitein. Isoflavone as found at highest concentration in plasma at 6 hours after oraladministration i.e: genistein of 11,17 ppm, daidzein of 2,86 ppm and glisitein of 2,47 ppm. Theadministration isoflavones at dose 2 mg/200g bw could decrease blood glucose levels in hyperglycemiarats, and also has hipocholesterolemia effect.
Keywords: isoflavone, hyperglycemia, blood of biochemistry